Analisis Pemasaran Karet Sistem Lelang di Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi - Dina Kurniati; Evy Maharani; Susy Edwina (Hasanuddin University, 2021)
This study aims to determine the marketing system in the auction market and analyze marketing costs, marketing margins, marketing profits, farmer’s share and marketing efficiency at the rubber auction market in Kuantan Mudik District. The sampling method used by farmers is purpusive sampling as many as 23 people and sampling traders using the census method as many as 8 people. The results show that the auction marketing system occurs because of the problems faced by farmers, namely long marketing channels and traders can control the price of bokar due to the low quality of bokar. Farmers participating in the auction market must meet the bokar quality standards set by the Kuantan Singingi Rubber Farmers Association (APKARKUSI) and join a farmer group or Gapoktan. Farmers have limitations in marketing bokar directly to factories, therefore farmers involve marketing agencies. Rubber marketing channels in the auction market are started from farmers-big traders-factories. Farmers who participate in the auction market are subject to a 5% reduction in bokar volume consisting of 3% depreciation, 1% transportation costs and 1% group operating costs. The selling price of bokar in July 2020 received by farmers was Rp7.367,50/kg, total marketing cost was Rp1.316,56/kg, marketing margin was Rp1.596,25/kg, marketing profit was Rp229,69/kg, farmer's share 82,19% and 14,69% marketing efficiency. This auction marketing system is efficiently used by farmers in the bokar marketing process in Kuantan Mudik District, because efficiency below 50% means the lower the percentage of marketing efficiency, the more efficient marketing.